Autophagy Improves the Immunosuppression of CD4+ T Cells by Mesenchymal Stem Cells Through Transforming Growth Factor‐β1. (11th July 2016) - Gao, Liangbin; Cen, Shuizhong; Wang, Peng; Xie, Zhongyu; Liu, Zhenhua; Deng, Wen; Su, Hongjun; Wu, Xiaohua; Wang, Shan; Li, Jinteng; Ouyang, Yi; Wu, Yanfeng; et al.
Abstract : Whether autophagy will affect the therapeutic efficacy of mesenchymal stem cells (MSCs) is largely unknown. It is demonstrated that autophagy could improve the immunosuppression of CD4 + T cells by MSCs through transforming growth factor‐β1. Therefore, regulation of autophagy in MSCs would provide a promising strategy to improve the therapeutic efficacy of these cells. Abstract : Acknowledgements: Mesenchymal stem cells (MSCs) have been extensively investigated as a promising approach to treat many autoimmune and inflammatory diseases. The stress condition would affect the therapeutic efficacy and induce autophagy of MSCs. However, whether autophagy would affect the immunosuppressive capacity of MSCs is largely unknown. The present study aimed to assess whether autophagy plays an important role in regulating the immunomodulation of MSCs and the undermechanisms. We successfully inhibited and induced autophagy of MSCs using 3‐methyladenine (3‐MA) and rapamycin, respectively. Our results demonstrated that rapamycin strengthened the capacity of MSCs to inhibit CD4 + T‐cell proliferation, whereas 3‐MA weakened the inhibitory ability of MSCs. Mechanistically, 3‐MA‐pretreated MSCs secreted less, whereas rapamycin‐pretreated MSCs secreted more transforming growth factor‐β1 (TGF‐β1) compared with the control cells. Furthermore, exogenous TGF‐β1 addition recovered the immunosuppressive capacity of 3‐MA‐pretreated MSCs, whereas exogenous anti‐TGF‐β1 antibody addition reduced the immunosuppressive capacity of rapamycin‐pretreated MSCs. These results indicated that the autophagy level regulates the immunosuppression of CD4 + T cells by MSCs through affecting TGF‐β1 secretion and provides a novel method for improving the therapeutic efficacy of MSCs by activating autophagy. Mesenchymal stem cell (MSC)‐based therapy is a promising tool to treat many diseases. Autophagy occurred in MSCs during their application, especially in those exposed to stress conditions. However, whether autophagy will affect the therapeutic efficacy of MSCs is largely unknown. This study makes a significant contribution to demonstrate that autophagy could improve the immunosuppression of CD4 + T cells by mesenchymal stem cells through transforming growth factor‐β1. Therefore, regulation of autophagy in MSCs would provide a promising strategy to improve the therapeutic efficacy of these cells.